PENGARUH CURRENT RATIO (CR) , DEBT TO ASSET RATIO (DAR), TERHADAP RETURN ON ASSET (ROA) PADA PT FAST FOOD INDONESIA TBK. PERIODE 2014-2023 - Mayanti, Erlis; Nuryani, Yusni (Journal of Research and Publication Innovation, 2024)
This study aims to determine the effect of Current Ratio and Debt to Asset Ratio on Return on Asset of PT Fast Food Indonesia Tbk for the period 2014-2023. The independent variables in this study are Current Ratio and Debt to Asset Ratio, while the dependent variable is Return on Asset. This research method is quantitative with analysis in the form of multiple linear regression. The data used are secondary data. The population in this study is the Financial Report of PT Fast Food Indonesia Tbk for the period 2014-2023. The sample used is the results of the Financial Report in the form of Balance Sheet and Profit and Loss Statement of PT Fast Food Indonesia Tbk for the period 2014-2023. Based on the results of the hypothesis, the Current Ratio results have a Tcount value <Table or (0.819 <2.306) and a significant value smaller than Sig. 0.05 or (0.440> 0.05) then Hol is accepted and Hal is rejected, this shows that the Current Ratio has no significant effect on Return on Asset. The results of the Debt to Asset Ratio hypothesis have a Tcount value > Ttable or (-1 .223 < 2.306). And the significant value is smaller than Sig. 0.05 or (0.261 > 0.05) then Ho2 is accepted and Ha2 is rejected, this shows that Debt to Asset Ratio has a significant negative effect on Return on Assets. And from the results of the F Test, the Fcount value is obtained > Ftable or (17.112 > 4.47) and the significant value is smaller than Sig, or 0.05 or (0.002 < 0.05) then Ho3 is rejected and Ha3 is accepted, this shows that simultaneously Current Ratio and Debt to Asset Ratio have a significant effect on Return on Assets.